EFFECT OF WEATHER AND AGROTECHNICAL CONDITIONS ON THE CONTENT OF NUTRIENTS IN THE FRUITS OF MILK THISTLE (Silybum marianum L. Gaertn.) - Jadwiga Andrzejewska; Katarzyna Sadowska; Małgorzata Woropaj-Janczak (Acta Scientiarum Polonorum: Hortorum Cultus, 2011)
Milk thistle (Silybum marianum L. Gaertn.) is recognized as a medicinal plant used for liver treatment. The aim of the present research was to determine the scope of variation in the content of nutrients in the fruits of milk thistle as a potential additive to animal feeds. The material was made up by whole achenes of thistle collected from the field experiment (2004–2006) carried out in Mochełek (53°13' N; 17°51' E). Two dates of sowing, three varied harvest methods and two sowing rates were applied. Weather conditions demonstrated a greater effect on the changes in the chemical composition than agrotechnical conditions. Changes in the content of total protein were least considerable, and those in the content of crude fibre and macroelements, especially calcium and magnesium – most considerable. The fruits contained, on average, 21.6% of fat in which linoleic acid accounted for 51.6% and total protein 16.1%, where glutamic acid was the dominant amino acid. The content of macroelements in g.kg-1 of d.m. was as follows: phosphorus – 6.1, potassium – 4.95, calcium – 7.6, magnesium – 2.6. A high content of iron was found – 82.3 mg.kg-1 of d.m. The fruits contained, on average (g.kg-1 of d.m.): 266.0 of crude fibre, 418.0 of NDF, 344.0 of ADF and 114.0 of ADL. Because of high content of cellulose-lignin fraction the whole fruits of milk thistle can be used only for ruminants.